Synthesis and antimicrobial activity of novel oxime derivatives of phenothiazine - Barve, Ashutosh; Noolvi, Malleshappa; Subhedar, Niharika; Gupta, Vishnu Dev; Bhatia, Gaurav (European Journal of Chemistry, 2011)
A series of 4-methyl-2-oxo-pyranyl-phenothiazines (IIIa-j) followed by 4-methylpyrano-(2, 3-β)-phenothiazine-2(11H)-one oxime (IVa-j) were synthesized by using 7-hydroxy-4-methylcoumarin (I). Further reaction of (I) was carried out with substituted aromatic amines (a-j) to convert into 7-arylamino-4-methyl-coumarin (IIa-j). Additionally (IIa-j) was treated with sulphur in presence of iodine to obtain a series of novel 4-methyl-2-oxo-pyranyl-phenothiazine (IIIa-j) derivatives, which on treatment with hydroxylamine hydrochloride afforded the title compounds i.e. 4-methylpyrano-(2,3-β)-phenothiazine-2(11H)-one oxime (IVa-j). The structures of these compounds were confirmed by IR, NMR and Mass spectral analysis. The newly synthesized compounds were evaluated for antibacterial and antifungal activity. The results show that compound IIIa, IIIe, IIIh, IIIj, IVa, IVi and IVj exhibited moderate to good antibacterial and antifungal activity at 5-100 mcg/mL.